2001
DOI: 10.1002/ijc.1572
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor mutation type iii transfected into a small cell lung cancer cell line is predominantly localized at the cell surface and enhances the malignant phenotype

Abstract: In the present study we transfected the epidermal growth factor receptor (EGFR)-negative small cell lung cancer cell line, GLC3, with the type III EGFR mutation (EGFRvIII). The EGFRvIII protein could be detected by Western blot analysis as a 145-kDa protein, which by immunohistochemistry appeared to be localized at the cell surface. Ultrastructurally EGFRvIII was expressed mainly at the cell surface with clusters at cell-cell contacts. In the in vitro invasion assay, GLC3-EGFRvIII cells had a Ϸ5-fold increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 41 publications
3
27
1
Order By: Relevance
“…Despite being unable to bind growth factors, this variant is constitutively phosphorylated and elicits downstream signaling qualitatively and quantitatively different from ligand-activated wild-type EGFR (Pedersen et al, 2001). EGFRvIII confers enhanced tumorigenicity (Damstrup et al, 2002) and has been detected, for example, in gliomas (57-86%) and in non-small cell lung cancer (NSCLC) (5-39%) (Moscatello et al, 1995;Okamoto et al, 2003;Ji et al, 2006).…”
Section: Egfr and Cancermentioning
confidence: 99%
“…Despite being unable to bind growth factors, this variant is constitutively phosphorylated and elicits downstream signaling qualitatively and quantitatively different from ligand-activated wild-type EGFR (Pedersen et al, 2001). EGFRvIII confers enhanced tumorigenicity (Damstrup et al, 2002) and has been detected, for example, in gliomas (57-86%) and in non-small cell lung cancer (NSCLC) (5-39%) (Moscatello et al, 1995;Okamoto et al, 2003;Ji et al, 2006).…”
Section: Egfr and Cancermentioning
confidence: 99%
“…[1][2] This mutant receptor is a constitutively activated, ligand-independent oncoprotein and has been detected in a variety of human cancers. [3][4][5][6][7][8] Early studies have shown that EGFRvIII appears to utilize downstream signaling pathways in a different manner from those of wild-type EGFR. [9][10][11][12] Furthermore, EGFR-overexpressing xenografts were sensitive to treatment with gefitinib (ZD1839), an EGFR-tyrosine kinase inhibitor, while EGFRvIII-expressing xenografts failed to respond to gefitinib treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The EGFRvIII is also capable of significantly enhancing the tumorgenicity of immortalized murine fibroblasts Moscatello et al, 1996) and the breast cancer cell line MCF-7 (Tang et al, 2000). Also, the EGFRvIII increases the in vitro invasiveness of a smallcell lung cancer cell line (Damstrup et al, 2002). Using the murine hematopoietic 32D cell line, Tang et al (2000) demonstrated that the EGFRvIII is capable of directly transforming a non-tumorigenic cell line.…”
Section: Introductionmentioning
confidence: 99%